Outpatient fluoroquinolone prescribing patterns before and after US FDA boxed warning. Issue 6 (11th May 2020) - Bratsman, Andrew; Mathias, Kristen; Laubscher, Rory; Grigoryan, Larissa; Rose, Stacey
Abstract: Objectives: Fluoroquinolones are routinely overprescribed for uncomplicated urinary tract infection (uUTI), acute sinusitis, and acute bronchitis. In 2016, the United States (US) Food and Drug Administration (FDA) updated the boxed warning on fluoroquinolones, recommending against their use as first‐line agents for the routine pharmacologic management of uUTI, acute sinusitis, and acute bronchitis in patients who have other treatment options. The primary objective of this study was to determine if the 2016 expanded boxed warning was associated with decreased fluoroquinolone prescription rates for these three diagnoses. Methods: We retrospectively reviewed antibiotics prescribed at a single, large, academic outpatient center for these three diagnoses between January 2013 and May 2018. Interrupted time series analysis was used to compare the rate of fluoroquinolone prescriptions before and after the May 2016 FDA boxed warning. Results: A total of 10 087 antibiotic prescriptions for these three diagnoses were examined. There was no significant change in fluoroquinolone prescription rates after the FDA boxed warning. The majority of inappropriate fluoroquinolone prescriptions were given for the management of uUTI. Conclusion: The 2016 US FDA boxed warning against fluoroquinolone use for uUTI, acute sinusitis, and acute bronchitis was not associated with a statistically significant reduction in the rate of fluoroquinolone prescriptions for these diagnoses. Additional research is needed to define how US FDA boxed warnings may be incorporated into broader antibiotic stewardship programs to decrease overuse of fluoroquinolones and avoid adverse effects of the drug class, including Clostridioides difficile infections and emergence of resistant organisms.